Dimer site-bond percolation on a triangular lattice. (6th February 2017) - Ramirez, L S; De la Cruz Félix, N; Centres, P M; Ramirez-Pastor, A J
Abstract: A generalization of the site-percolation problem, in which pairs of neighbor sites (site dimers) and bonds are independently and randomly occupied on a triangular lattice, has been studied by means of numerical simulations. Motivated by considerations of cluster connectivity, two distinct schemes (denoted as S ∩ B and S ∪ B ) have been considered. In S ∩ B ( S ∪ B ), two points are said to be connected if a sequence of occupied sites and ( or ) bonds joins them. Numerical data, supplemented by analysis using finite-size scaling theory, were used to determine ( i ) the complete phase diagram of the system (phase boundary between the percolating and nonpercolating regions), and ( ii ) the values of the critical exponents (and universality) characterizing the phase transition occurring in the system.